Exploring The Impact of Muslim Students' Religiosity on Indonesian Local Wisdom - Lestari, Wahyu; Wisudaningsih, Endah Tri (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
The research aims to explore the influence of Muslim students' religiosity on local wisdom in Indonesia. Employing a quantitative approach, the study distributed questionnaires to 1026 students. The sample was selected using purposive sampling, specifically targeting Muslim students practicing moderate Islamic teachings. Five dimensions of religiosity were assessed: spirituality (X1), ideological (X2), intellectual (X3), experiential (X4), and consequential (X5). Multiple linear regression was utilized to estimate the impact of these dimensions. Findings indicated a positive correlation between students' religiosity and Indonesian local wisdom. Empirical evidence revealed that only three dimensions of religiosity—ideological, intellectual, and consequential—significantly and positively influenced local wisdom. Among these, the consequential dimension exhibited the highest impact, with a regression coefficient of 2.13. Conversely, spirituality and experiential dimensions showed positive but statistically insignificant effects. The implication is that Muslim students with open-minded and flexible attitudes represent valuable social assets in preserving Indonesia's local wisdom values.